从前有个骰子 Once Upon a Time There was a DICE - Siaw San, Loh; Kuan, Wee Ling (Xiao Studio (AS0465798-A), 2026)
The Chinese New Year is rich in vibrant cultural stories. If readers can learn about traditional Chinese festivals while having fun, why not? So, we came up with an idea: combining words with a chessboard. We named the little book "Once Upon a Time" (legendary stories), there was a DICE (board game). With each roll of the dice and every small step taken, it conveys the cultural essence passed down through generations.